2003
DOI: 10.1161/01.cir.0000093195.73667.52
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Pulmonary Venous Flow in the Fetus and Its Association With Vascular Diameter

Abstract: Background-The usual positioning of the Doppler sample volume to assess fetal pulmonary vein flow is in the distal portion of the vein, where the vessel diameter is maximal. This study was performed to test the association of the pulmonary vein pulsatility index (PVPI) with the vessel diameter. Methods and Results-Twenty-three normal fetuses (mean gestational age, 28.6Ϯ5.3 weeks) were studied by Doppler echocardiography. Pulmonary right upper vein flow was assessed adjacent to the venoatrial junction ("distal"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…However, large cardiology centres usually have well-structured programmes of fetal cardiology with advanced techniques for the diagnosis and even treatment of some CHD in utero. Interesting clinical research has been performed on several cardiac fetal topics, including screening of CHD in selected pregnant women, abnormalities of the septum primum, cardiovascular abnormalities in fetuses of diabetic mothers, diastolic dysfunction, restriction of flow across the foramen ovale, treatment of fetal arrythmias and fetal interventions for aortic stenosis and hypoplastic left heart syndrome 545100101102103104105106107108109110111112113…”
Section: Outcomes After Medical Surgical or Interventional Treatmentmentioning
confidence: 99%
“…However, large cardiology centres usually have well-structured programmes of fetal cardiology with advanced techniques for the diagnosis and even treatment of some CHD in utero. Interesting clinical research has been performed on several cardiac fetal topics, including screening of CHD in selected pregnant women, abnormalities of the septum primum, cardiovascular abnormalities in fetuses of diabetic mothers, diastolic dysfunction, restriction of flow across the foramen ovale, treatment of fetal arrythmias and fetal interventions for aortic stenosis and hypoplastic left heart syndrome 545100101102103104105106107108109110111112113…”
Section: Outcomes After Medical Surgical or Interventional Treatmentmentioning
confidence: 99%
“…No antegrade flow was detected in the middle part of the pulmonary vein in 3% and in the distal part in 16% . Moreover, Zielinsky et al showed that pulmonary venous flow pulsatility increases as a result of the increasing vascular narrowing in the venoatrial region of the heart toward the periphery of the lung …”
Section: Discussionmentioning
confidence: 93%
“…Possible reasons for this correlation are the highly specific IUGR population due to placental dysfunction and the lack of stratification based on placental insufficiency in group 2. The use of pulmonary vein PI in fetuses has been proposed as a good echocardiographic Doppler parameter to assess fetal cardiac dynamics [12,29] since it reflects LA pressure changes and is reproducible [17]. IUGR fetuses showed an increased PVPI, reflecting flow distribution in the left heart with changes in LA pressure, probably due to left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the pulmonary venous flow, the Doppler sample volume was placed at the right superior pulmonary vein adjacent to the veno- atrial junction ("distal position") in a 4-chamber view, guided by color-flow mapping or power-angio Doppler [17] with an angle of insonation < 30°. Scales of 0-20 cm/s and filters of 50-100 Hz were used and 3 measurements were obtained in apnea.…”
Section: Methodsmentioning
confidence: 99%